Tom Clancy full force and effect [compact disc, unabridged] - Greaney, Mark (Books on Tape ; Random House Audio, 2014)
A North Korean ICBM crashes into the Sea of Japan. A veteran CIA officer is murdered in Ho Chi Minh City, and a package of forged documents goes missing. The pieces are there, but assembling the puzzle will cost Jack Ryan, Jr. and his fellow Campus agents precious time. Time they don't have.